Zen of the Plains : Experiencing Wild Western Places - Olstad, Tyra A. (Book collections on Project MUSE., 2014)
Although spare, sweeping landscapes may appear ""empty, "" plains and prairies afford a rich, unique aesthetic experience--one of quiet sunrises and dramatic storms, hidden treasures and abundant wildlife, infinite horizons and omnipresent wind, all worthy of contemplation and celebration.